The potato genome - Chakrabarti, Swarup Kumar; Xie, Conghua; Tiwari, Jagesh Kumar (Springer, 2017)
This book describes the historical importance of potato (Solanum tuberosum L.), potato genetic resources and stocks (including S. tuberosum group Phureja DM1-3 516 R44, a unique doubled monoploid homozygous line) used for potato genome sequencing. It also discusses strategies and tools for high-throughput sequencing, sequence assembly, annotation, analysis, repetitive sequences and genotyping-by-sequencing approaches. Potato (Solanum tuberosum L.; 2n = 4x = 48) is the fourth most important food crop of the world after rice, wheat and maize and holds great potential to ensure both food and nutritional security. It is an autotetraploid crop with complex genetics, acute inbreeding depression and a highly heterozygous nature. Further, the book examines the recent discovery of whole genome sequencing of a few wild potato species genomes, genomics in management and genetic enhancement of Solanum species, new strategies towards durable potato late blight resistance, structural analysis of resistance genes, genomics resources for abiotic stress management, as well as somatic cell genetics and modern approaches in true-potato-seed technology. The complete genome sequence provides a better understanding of potato biology, underpinning evolutionary process, genetics, breeding and molecular efforts to improve various important traits involved in potato growth and development.
Keywords: Potatoes -- Genome mapping.; Potatoes -- Disease and pest resistance.; elektronické knihy; electronic books